Abuse of privileged information of government employees (crime of) - Otero González, Pilar (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The analysis of the various elements from which it is defined the crime of abuse of privileged information of government employees constitutes the aim of this work. This analysis extends to juridical protected goods – the integrity of the function and the protection of the general interest-; to the active agent – the government employee who legally access to the privileged information or secret-; to the normal action – the use of the secret or the privileged information for personal benefit-; to the object itself – the secret and/or privileged information-; and, finally, to its termination – produced by the simple use of the secret or the privileged information with the intention of obtaining any economic benefit. Finally, the author examines the content of the penal responsibility, autonomously foreseen, of the particulars that were favored by this action.